1988
DOI: 10.1021/ma00182a032
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-limited phosphorescence quenching interactions in polymer solutions: small molecule-small molecule interactions interpreted by free volume theory

Abstract: Diffusion-limited interactions between benzil and anthracene were studied by phosphorescence quenching in polystyrene-cyclohexane, polystyrene-toluene, poly(methyl methacrylate)-toluene, and polybutadiene-cyclohexane solutions. Values of the bimolecular diffusion-limited quenching rate constant, kq, were obtained by measuring benzil phosphorescence lifetime as a function of anthracene concentration and applying a Stern-Volmer analysis. Besides polymer species and solvent, k" was measured as a function of polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 6 publications
(6 reference statements)
2
15
0
Order By: Relevance
“…Further contributions to the field of phosphorescence quenching have come from the group of Torkelson (104,117,(190)(191)(192)(193)196). Although they pointed out several weak aspects in the work of Horie and Mita regarding their polymer synthesis and data analyses (196), their findings with respect to the ratio of the rate of S-S quenching versus S-L quenching (196) and the scaling of k q with cooperative diffusion in the dilute regime (104) were similar to those of Horie and Mita.…”
Section: De Kock Van Herk and Germanmentioning
confidence: 73%
See 2 more Smart Citations
“…Further contributions to the field of phosphorescence quenching have come from the group of Torkelson (104,117,(190)(191)(192)(193)196). Although they pointed out several weak aspects in the work of Horie and Mita regarding their polymer synthesis and data analyses (196), their findings with respect to the ratio of the rate of S-S quenching versus S-L quenching (196) and the scaling of k q with cooperative diffusion in the dilute regime (104) were similar to those of Horie and Mita.…”
Section: De Kock Van Herk and Germanmentioning
confidence: 73%
“…Among other things, they focused on the inter-and intramolecular quenching of a copolymer containing a small fraction of phenyl vinyl ketone. Results of the previously mentioned phosphorescence quenching technique, for instance, have shown that this is not an unreasonable assumption as polymer only acts as an obstacle for diffusion of small molecules (189)(190)(191)(192)(193) and references therein). † This is again in agreement with Eq.…”
Section: Diffusion-controlled Mimic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To accomplish this study, two complementary and relatively little-employed techniques are used to obtain information on diffusion: Taylor dispersion [47][48][49][50][51][52][53][54][55] and phosphorescence quenching. 56,57 Taylor dispersion is a rapid and relatively inexpensive technique based on the dispersion of a solute in a liquid undergoing laminar tube flow. The theory was first discussed by Taylor, 47,48 and later by Aris, 49 and was applied by Ouano, 50 who demonstrated that the solute diffusion coefficient in a two-component system can be determined from the mean, t h, and variance, σ 2 , of the solute concentration profile as it exits the tube.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorescence quenching, a useful tool in obtaining information on diffusion-limited interactions in concentrated polymer solutions, is employed to determine the bimolecular quenching rate constant, k q , associated with the reduction of phosphorescence intensity with the addition of quencher, as a function of polymer concentration. Previous studies 19,56,57 have shown that for interactions involving small molecules k q can be related to the self-diffusion coefficients of the chromophore, D c , and quencher, D q , through the modified Smoluchowski equation: 58 where F is a steric factor taken to be 0.5, R T is the encounter radius between chromophore and quencher, and N A is Avogadro's number per millimole. Small molecule-polymer interactions have also been studied using phosphorescence quenching.…”
Section: Introductionmentioning
confidence: 99%